Where grief lingers: Agnes’s journey through loss in Maggie O’Farrell’s Hamnet - Natalie Anabella Harinda; Maria Johana Ari Widayanti (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
Death and loss, no matter how common at the time, are personal and emotionally tolling. Written as historical fiction, Hamnet tries to fill the gap in the history of the death of Shakespeare’s son, Hamnet, during the bubonic plague in late 16th-century England. Investigations into the novel Hamnet, particularly concerning Agnes and her grief journey as the protagonist, have not been previously conducted, so this study seeks to address this gap and examine grief with a focus on Agnes. This research intends to explore Agnes's journey through grief and how her feelings of loss influence her relationships with those around her. Faced with the death of her son, Hamnet’s protagonist followed the Kübler-Ross trajectory of stages of grief: denial, anger, bargaining, depression, and acceptance, though some emotions may emerge due to a trigger. The research indicated that the most significant stage of grief that Agnes went through was the depression phase, as it profoundly impacted her sense of identity and her relationships. Apart from acceptance, these grief stages, manifestations of emotional responses to grief, brought damage to Agnes’s relationship with other people. Conversely, the acceptance stage brought conciliation to the relationship.